Antimicrobial susceptibility of microorganisms causing Urinary Tract Infections in Saudi Arabia - Bander Balkhi; Wael Mansy; Sultan AlGhadeer; Abdulrahman Alnuaim; Abdullah Alshehri; Ali Somily (Journal of Infection in Developing Countries)
Introduction: Urinary Tract Infections (UTIs) is one of the most common infections worldwide. UTIs remain a challenge to the healthcare system because of the emergence of antimicrobial resistance. The aim of this study is to report the most common UTI-causative organisms associated with the emergence of antimicrobial resistance in Saudi Arabia.